IMPULSIVITY AND SELF-HARM BEHAVIOR IN YOUNG ADULT WOMAN WITH AUTHORITATIAN PARENTING: A CASE REPORT - Asy Syifa Karima; Zuhrotun Ulya (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Introduction: Authoritarian parenting is a risk factor for impulsive behavior and children's self-efficacy. The maladaptive behavior of a teenager is influenced by many factors, including parenting, family and friendships. This can cause various psychological problems.Case report: A 21-year-old woman with impulsive behavior and selfharm turned out to have authoritarian parenting and a genetic history.Methods: data were taken from interviews and mental status examinations in psychiatric clinics, then a literature review was carried out.Result and Discussion: Both permissive and authoritarian parenting styles led to personality disorders. Authoritarian parenting has a negative impact on the adaptation of behavior and personality of children in adolescence and can persist into adulthood if not handled properly. In addition to parenting, genetics and the environment also influence adolescence.